Accompaniment from the Guidance from students of Technical Education institutions - Murillo Aguilar, Osvaldo (2023)
This article arises within the framework of Project 724-C1-714, Thematic Observatory of Costa Rican Professional Technical Education and Training, registered in the Institute of Research in Education of the University of Costa Rica. Given the nature of the Guidance service in Costa Rican educational institutions, the results of the research named: Accompaniment made by guidance counselors to the students at Professional Technical Colleges (CTP) for the election of an Educación y Formación Técnica Profesional EFTP institution and the specialty they want to enroll in, are presented. This is a qualitative study with a descriptive scope and a phenomenological method. Structured interviews were used, and seven CTP guidance counselors from different educational regions participated. The accompaniment that the guidance counselor provides to the students for the choice of the institution and specialty was defined as a dimension. The information obtained was grouped into five categories: Strategies used for accompaniment, Accompaniment role of the professional guidance counselor, Accompaniment Success, limitations of accompaniment, and Considerations for accompaniment. In conclusion, the definition of the functions of the group of Guidance counselors does not distinguish between academic and EFTP institutions, the guidance lesson is not taught in the diversified education of the CTP, and the Vocational Fair is one of the strategies used in the accompaniment of the CTP students. As opportunities for improvement, it is mentioned importance of taking advantage of support strategies to involve the student's family further.